Hubungan Tipe Kepribadian Berdasarkan Big Five Theory Personality dengan Kebimbangan Karier pada Siswa SMA - Salma Aulia Utami; Novika Grasiaswaty; Sari Zakiah Akmal (Jurnal Online Psikogenesis, 2018)
Making decision related to choosing a major in university is a complecated process for senior high school students (grade XII), particularly for those with career indecision problem. Career indecision is persons inability to choose a particular course of study. Some studies showed that personality is one of significant factor that correlate with career indecision. However, there are some incosistency related to the particular aspec of personality which is associated with career indecision. This research was conducted to find out the relationship of personality type based on big five theory personality with career indecision among high school students of class XII in Jadebotabek. The sample involved 128 high school students which obtained by using incidental sampling technique. The data were collected by using Career Decision Scale (CDS) and Big Five Inventory (BFI) measurements. The results showed that there was a positive relationship between neurotics (r = 0.175) with career indecision and negative relationship between conscientiousness (r = -0.181) with career indecision variable. While other dimensions such as: openness to experience, extraversion, and agreeableness has no significant relationship with career indecision. Thus, an intervention to help students with career indecision problem need to consider aspec of personality.Â